Kinetics and Mechanism of Oxidation of Phenols by Pyridinium Fluorochromate in Glacial Acetic Acid - Patil, S.G.; Joshi, S.B. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of phenols such as p-hydroxy benzoic acid, p-chloro phenol, m-cresol, p-nitrophenol and p-cresol has been investigated, in glacial acetic acid as a solvent in the temperature range 25–45ºC, using pyridinium fluorochromate (PFC) as a mild oxidation agent. The overall order of oxidation of the phenols is found to be two and the individual order as one in each reactant [the stoichiometry of the reaction is 1 : 1]. An increase in solvent polarity increases the reaction rate. The activation energy and other thermodynamic parameters are determined. A probable reaction mechanism is proposed.